Cuidados prenatales en pacientes con hipertensión gestacional atendidas en el centro de salud de puertas negras del cantón Babahoyo, provincia de Los Ríos, en el primer semestre del 2018 - Bustos Veliz, Helen Denis (2018)
The present investigation justifies due to the need to determine the association between prenatal care and maternal-fetal complications in patients diagnosed with Gestational Hypertension attended at the Puertas Negras Health Center, during the first half of 2018. It is necessary protocolize the care of these patients to prevent the development of complications and safeguard the integrity and the state of health in general. The research was carried out at the Puertas Negras Health Center in the city of Babahoyo during the first semester of this year. The present study has a quantitative approach, through a descriptive, correlational and cross-sectional investigation, the techniques of direct observation and collection of statistical data, as well as Ballard's scale as an instrument. It is concluded that there is a strong increase in the risk of developing this pathology in pregnant women who have a history of arterial hypertension prior to pregnancy, followed by a much lower prevalence, the history of cases of first-degree relatives with this condition and a body mass index compatible with obesity in these patients. It is recommended to carry out prevention and socialization campaigns about the risk of developing gestational hypertension among pregnant women